2018
DOI: 10.13005/bpj/1579
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Risk Factor Profile for Enucleated Retinoblastoma at Sanglah General Hospital

Abstract: Retinoblastoma is a primary intraocular tumor on childhood. It has a good prognosis with early detection. Aim of this study is to know Pathological Risk Factors (PRF) profile of enucleated retinoblastoma at Sanglah General Hospital. This study is an observational retrospective study based on patient’s medical record and pathological examination. Twenty patients were included in this study, 50% were female and 50% male within age ranging from 7 month – 12 years old. Unilateral retinoblastoma was found in 18 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 12 publications
4
4
0
Order By: Relevance
“…Our study reported most of RB diagnosed at 25-36 months (32.2%). In developed countries, such as USA and Britain, RB is diagnosed early in childhood at an average age of 18 months, while the diagnosis occurs later in developing countries [2,24], such as in Indonesia [5,25]. Sixty-six patients were female, consistent with the study of Singh et al [26] and Owoeye et al [27] who described a higher incidence of RB in females than males.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Our study reported most of RB diagnosed at 25-36 months (32.2%). In developed countries, such as USA and Britain, RB is diagnosed early in childhood at an average age of 18 months, while the diagnosis occurs later in developing countries [2,24], such as in Indonesia [5,25]. Sixty-six patients were female, consistent with the study of Singh et al [26] and Owoeye et al [27] who described a higher incidence of RB in females than males.…”
Section: Discussionsupporting
confidence: 81%
“…According to the laterality, unilateral RB is more common than bilateral RB [2,24,30], as observed in this study with more unilateral cases than bilateral cases. Another study conducted in Indonesia by Yuliawati and Ekawati [5] also showed a similar result.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations